Capitalist dynamics: fictional expectations and the openness of the future - Beckert, Jens (Köln, 2014)
"Capitalism is an economic and social order oriented toward the future. In this paper, I describe the unfolding of the temporal order of capitalism and relate it to the restless dynamism of capitalism we have observed since the Industrial Revolution. Since the future is open, actors are confronted with the uncertainty of the outcomes of their decisions. What can expectations be under conditions of uncertainty? To answer this question, I introduce the notion of fictional expectations which can be used to describe decisions made under conditions of an open and uncertain future. In the paper's penultimate section, I apply the concept of fictional expectations to the analysis of four crucial processes of capitalism: money and credit, investments, innovation, and consumption. The main thrust of the paper is that in order to understand economic action in capitalism, actors' perceptions of the future need to take center stage. Not only "history matters," but also the "future matters."